Αφήγηση μέσω περιβάλλοντος: Ένα animatic - Νικολάου, Ντάνιελ (My University, 2024)
Exploring the realm of storytelling within animation, this thesis delves into the nuanced dynamics of utilizing backgrounds as the central conduit for narrative conveyance. Through a comprehensive fusion of theoretical analysis and practical experimentation, the research endeavors to dissect the creative potentials and inherent constraints inherent in employing backgrounds as the primary storytelling medium in animated film. A thorough investigation is conducted, encompassing a literature review alongside practical endeavors such as the construction of an animatic, an image sequence instrumental in narrative establishment and progression. Commencing with a meticulous examination of layout techniques in animation, the thesis proceeds to scrutinize various case studies spanning films, television productions, and video games, wherein layout assumes a paramount role in narrative construction. The resultant analysis furnishes a corpus of guiding principles, subsequently harnessed during the practical phase of animatic development. Furthermore, the inquiry yields invaluable insights into the strategic placement of models, encompassing both objects and characters, within the spatial frameworks delineated by the backgrounds. Integral to this exploration is an examination of disparate mediums, facilitating a nuanced understanding of diverse storytelling methodologies and the adept utilization of environmental cues for narrative augmentation. The study aspires to enrich comprehension surrounding animation as an expressive art form, shedding light on the efficacious utilization of landscapes and visual metaphors as conduits for narrative explication. In sum, this academic endeavor seeks to contribute substantively to the scholarly discourse surrounding animation, advancing insights into the multifaceted interplay between background-centric storytelling and the narrative fabric of animated compositions.
Keywords: Scene Planning; Animatic; Storytelling without characters; Διάταξη; Φόντο; Σχεδιασμός Σκηνής; Ανιμάτικ; Αφήγηση χωρίς χαρακτήρες